جمال اللغة القرآنية في سورة الكوثر - حاقة, عبد الكريم (جامعة الوادي - University of Eloued, 2022)
ملخص: اللغة القرآنية لغة راقية، تسمو على كلام البشر، لها خصائصها الصوتية والصرفية والتركيبية والبلاغية المميزة، وهذه الورقة البحثية تعالج موضوع اللغة القرآنية وإيحاءاتها في سورة الكوثر، لذا كان عنوانها: جمال اللغة القرآنية في سورة الكوثر، بحيث تحاول الإجابة عن الإشكال الآتي: ما الأسرار وما الإيحاءات التي توحي بها الأصوات والكلمات والتراكيب اللغوية في سورة الكوثر؟ وقد تناولت في هذه الورقة البحثية التعريف بالسورة الكريمة، وتفسيرها، ثم عرضت للأصوات وما توحي به، ثم تناولت المفردة القرآنية وإيحاءاتها في السورة، ثم تكلمت عن التراكيب، ثم تعرضت للجوانب البلاغية، وقد اتبعت منجا وصفيا تحليليا، وخلصت إلى النتائج الختامية، وأهما أن الأصوات والألفاظ والتراكيب قد أوحت بدلالات تتفق والمعنى العام للسورة الكريمة. Abstract: The Qur’anic language is a sublime language that transcends human speech. It has distinctive phonetic, morphological, structural and rhetorical characteristics. This research paper deals with the subject of the Qur’anic language and its implications in Surat Al-Kawthar, so its title was: The Beauty of the Qur’anic language in Surat Al-Kawthar, as it attempts to answer the following problem: What are the secrets What are the revelations that the sounds, words and linguistic structures in Surat Al-Kawthar suggest? In this research paper, I dealt with the definition of the Noble Surah, and its interpretation, then presented the sounds and what it suggests, then dealt with the Qur’anic vocabulary and its implications in the surah, then talked about the structures, then exposed to the rhetorical aspects, and it followed a descriptive and analytical approach, and concluded to the final results, and most importantly that The sounds, words and structures have revealed semantics that are consistent with the general meaning of the noble surah.
مقال
Keywords: القرآن ؛ اللغة؛ الإيحاء؛ الأصوات؛ التراكيب؛ البلاغة; Quran language, connotation, sounds, words, syntax, rhetori